2016
DOI: 10.1192/pb.bp.115.052373
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for community treatment orders – a battle fought with heavy weapons

Abstract: This editorial discusses the pros and cons of community treatment orders (CTOs) from the perspective of community general adult psychiatry. There is little scientific evidence supporting the application of CTOs. Preconditions of a CTO to work are likely to be met by few patients. The time for the application of a CTO may be better spent for patient-centred care until there is sufficient new and robust evidence that identifies the patients that might profit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…However, the profile of the patients in the trials matches closely those on CTOs across countries (Burns 2013; Rugkåsa 2015). According to Heun and colleagues (2016), and we would agree, given the current evidence base the onus should now be on proponents of CTOs to identify, with some scientific rigor, which subgroup would benefit.…”
Section: Why Is the Evidence Still Debated?mentioning
confidence: 84%
See 1 more Smart Citation
“…However, the profile of the patients in the trials matches closely those on CTOs across countries (Burns 2013; Rugkåsa 2015). According to Heun and colleagues (2016), and we would agree, given the current evidence base the onus should now be on proponents of CTOs to identify, with some scientific rigor, which subgroup would benefit.…”
Section: Why Is the Evidence Still Debated?mentioning
confidence: 84%
“…Issues of attrition, protocol violations and crossovers are undoubtedly limitations of the RCTs (as with most pragmatic trials). However, it is highly unlikely that all of the RCTs and meta-analyses would have resulted in false-negative findings (Heun 2016). Given the exceptionally clear nature of these findings, reservations do not give cause for concern in the way they would have if the results had been approaching statistical significance (Szmukler 2015).…”
Section: Why Is the Evidence Still Debated?mentioning
confidence: 99%
“…Conversely, CTO opponents argue that one cannot see a probabilistic outcome that takes months to manifest itself and that the use of CTOs should be halted based on the negative findings of the RCTs . These sharply opposing stances have resulted in a state of apparent dissociation between academic research and clinical practice …”
Section: Community Treatment Ordersmentioning
confidence: 99%
“…58,63,64 These sharply opposing stances have resulted in a state of apparent dissociation between academic research and clinical practice. [65][66][67]…”
Section: Introductionmentioning
confidence: 99%
“…Communitycounselling could also be imposed. In the nearly three decades since CTOs were introduced in Victoria, three large-scale, randomized control trials and their meta-analyses have indicated that CTOs are ineffective in achieving their two principal aims: (1) lowering hospitalization rates or (2) protecting individuals subject to them (Heun, Dave, and Rowlands 2016), though no such studies have examined CTO-use in Australia. However, there is some evidence that CTOs were associated with reduced mortality rates, even when taking into consideration the use of community services, age, gender, inpatient experience, and diagnosis (Segal and Burgess, 2006).…”
Section: Introductionmentioning
confidence: 99%